THE DISINFODEMIC MITIGATION STRATEGY OF MAFINDO IN INDONESIA - Syarifah Ema Rahmaniah; Septiaji Eko Nugroho; Rupita; Nikodemus Niko (International Journal of Social Science, 2022)
Social media is usually utilized for literacy and education in articulating ideas and criticism. This study focused on the utilization of social media in the community during the COVID-19 outbreak, the implications for critical political awareness, and the wise use of social media. The data used was a compilation of hoax data circulating in Indonesia from independent fact-checking sites, government-run fact-checking sites, and fact-checking channels created by the mainstream media. The results revealed that the strong political polarization among the people was the cause of the massive spread of false news and hate speech during the COVID-19 outbreak. This study also described the mitigation strategy of MAFINDO to improve information security in facing an event that leads to an information crisis during the COVID-19 pandemic. Therefore, disinfodemic mitigation strategy was constructed as part of an early warning system in increasing public immunity against disinfodemic and controlling the spread of public suggestions and dangerous reactions. This study can be used an early warning system to prevent health misinformation by revitalizing the movement of the anti hoax community in online and offline education.